N04 Anaplerotic Therapy Using Triheptanoin Improves Brain Energy Metabolism In Patients With Huntington Disease. (17th September 2014) - Adanyeguh, IM; Rinaldi, D; Henry, P; Caillet, S; Valabregue, R; Durr, A; Mochel, F
Abstract : Background: Energy deficit has been implicated in the pathophysiology of Huntington disease (HD). Our previous work indicated a possibility of improving energy deficit by providing substrates to the Krebs cycle using anaplerotic therapies. Aims: Here our goal was to obtain a proof-of-concept of the therapeutic benefit of triheptanoin in an open-label study using a functional biomarker of brain energy metabolism validated in HD. Methods: 31P brain magnetic resonance spectroscopy (MRS) was used to measure the levels of PCr and Pi before (rest), during (activation) and after (recovery) a visual stimulus. We performed 31P brain MRS in 10 patients at an early stage of HD and 13 controls. HD patients were then treated for one month with triheptanoin after which they returned for follow-up including 31P brain MRS scan. Results: At baseline, we confirmed an increase in Pi/PCr ratio during brain activation in controls -- reflecting increased ATP synthesis -- followed by a significant return to baseline levels during recovery (p = 0.003). In HD patients, we validated the existence of an abnormal brain energy profile as previously reported. After one month, this profile remained abnormal in HD patients without treatment. Conversely, the MRS profile was significantly improved in HD patients treated with triheptanoin for one month with the restoration of an increased Pi/PCr ratio during visual stimulation (p = 0.004). Conclusions: This study suggests that triheptanoin is able to correct the bioenergetic profile in the brain of HD patients at an early stage of the disease.